(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
The problems faced by seed supply institutions are after the breaking of dormancy, seeds cannot be germinated immediately, but can be stored for an indefinite period of time until there is consumer demand. It is expected that seed storage for a certain period of time will still have good viability to be used as seeds. The aim of the study was to determine the viability response of oil palm seeds (Elaeis guineensis Jacq, L.) at various seed shelf lives and heating times. The study design used factorial in randomized groups with 3 replications. The first factor is seed shelf life: S1 = 0-6 months, S2 = 7-13 months, S3 = 14-20 months, S4 = >21 months, and reheating time as the second factor consists of 8 levels, namely: P1 = 20 days, P2 = 30 days, P3 = 40 days, P4 = 50 days, P5 = 60 days, P6 = 70 days, P7 = 80 days, and P8 = 90 days. Each treatment combination used 100 seeds. Data were analyzed using the SAS version 6 program, followed by honest significant difference test (BNJ) and regression analysis. The conclusion of this study is that the maximum storage time for oil palm seeds is Ëƒ 21 months, they can still be used as normal quality seeds. Effect of the best heating time on normal germination of seeds at 70 days of heating. The best treatment for seed storage is 0-6 months, with a heating time of 70 days.